Ag Nanoparticles Obtained by Green Synthesis as Bactericidal Agents in Water-Based Paints - Gomez de Saravia, Sandra Gabriela; Rastelli, Silvia Elena; Gamez Espinosa, Erasmo; Bellotti, Natalia; Deya, Cecilia; Viera, Marisa (New Environmentally-Friendly Materials, 2026)
To control the proliferation of microorganisms and its associated risks, protective surface coatings are being developed. Among the most promising solutions is the incorporation of silver nanoparticles (AgNPs) into paint formulations. Traditional physical and chemical nanoparticles synthesis pose health and environmental risks. The concept of “green nanoparticles” refers to the synthesis of nanoparticles using environmentally benign routes. The aim of this work was to obtain silver nanoparticles (AgNPs) using a green synthesis technique, incorporate them into a polymeric coating, and evaluate their effectiveness as a potential hygienic paint against both gram-positive and gram-negative bacteria. AgNPs were obtained by adding Schinopsis balansae (TS) or Caesalpinia spinosa (TC) tannin solution to an aqueous solution of AgNO3. The AgNPs were characterized by UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy, scanning electron microscopy, and energy dispersive X-Ray spectroscopy. A polymeric coating was formulated with nanoparticles. To evaluate the antibacterial coating efficiency, the modified ISO 22196 method was applied. The concentration and origin of tannin are factors that influence the size and polydispersity of the NPs; TS-AgNPs exhibited higher polydispersity than TC-AgNPs. Coatings incorporating TC-AgNPs exhibited the highest antibacterial efficacy, inhibiting all bacterial strains except Bacillus cereus. These results support the feasibility of integrating eco-friendly AgNPs into polymeric coatings for biodeterioration control in indoor environments.